Innovative Methods in Teaching English to High School Students - Aziza Safaralieva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores innovative methods used in teaching English to high school students in the context of modern education. It emphasizes that innovation in teaching not only involves technology but also pedagogical creativity, learner-centered approaches, and motivational strategies. The paper discusses techniques such as communicative language teaching, task-based learning, blended learning, gamification, and project-based instruction as key tools for developing language proficiency and motivation among students.